Analysis Of Vocational Students' Mathematics Learning Motivation In The 3T Region of West Halmahera - Rahim, Abdurrachman; Azka, Dea Alvionita; Maharani, Andika Ellena Saufika Hakim; Dwikasari, Lingga Gita (Universitas Wiralodra, 2024)
The level of students’ motivation to learn mathematics has an impact on mathematics learning outcomes. This research aims to identify the level of student learning motivation in mathematics learning for vocational school students in the frontier, outermost, and disadvantaged (3T) area. The type of research used was qualitative research with descriptive methods. The subjects of this research were 16 students from the 12th grade of Formarimoi Vocational School, West Halmahera. The data collection technique used was the distribution of questionnaires and classroom observations. Data analysis was carried out by calculating the average score and percentage of students' answers based on predetermined indicators which were then interpreted into assessment categories. Based on the research results, it was found that student learning motivation had a percentage score of 77.09% which was in the good category. In more detail, the indicator of feeling happy and diligent in learning has a percentage score of 78.90% in the good category, the indicator of willingness and interest in learning has a score of 74.41% in the good category, the indicator of self-confidence and independence in learning has a percentage score amounted to 69.87%, and the achievement indicator in learning had a score of 85.16% in the very good category.